Performance measurement of the upgraded Microcab-H4 with academic drive cycle - Rais, Luthfi; Fisher, Peter; Dhir, Aman; Steinberger-Wilckens, Robert (Communications in Science and Technology, 2016)
The original Microcab-H4, a hybrid fuel cell car, was tested with Academic drive cycle. After several years, the car was upgraded and tested with the ECE 15 drive cycle. The result showed the car has higher energy efficiency. However, the result could not be compared to the original car due to different drive cycle test. This research was done to measure the performance and energy efficiency of the Upgraded Microcab-H4 with Academic drive cycle. The measure of car energy efficiency was done through four tests: Run on battery, run on battery and Ballard fuel cell, and run on battery, Ballard, and Horizon fuel cell. The energy efficiency was calculated based on the hydrogen consumption after 5 cycles. The lowest energy efficiency was run on battery and Ballard fuel cell with (1.01 km/MJ). The highest energy efficiency was run on battery, Ballard, and Horizon fuel cells (1.10 km/MJ), which is higher than previous tests.